Decreased peripheral basophil counts in urticaria and mouse model of oxazolone-induced hypersensitivity, the latter suggesting basopenia reflecting migration to skin - Kishimoto, Izumi; Ma, Ni; Takimoto-Ito, Riko; Nakashima, Chisa; Otsuka, Atsushi; Walls, Andrew F.; Tanizaki, Hideaki; Kambe, Naotomo (Frontiers in Immunology, 2022)
A decrease in the number of basophils in the peripheral blood, or basopenia, has been noted, reflecting the activity of chronic spontaneous urticaria (CSU). Infiltration of basophils into the skin has also been reported, but the mechanism of basopenia in CSU has not been clarified. The phenomenon of basopenia during the active phase of urticaria was confirmed, and basophil numbers increased following symptom improvement in 15 out of 17 patients treated with omalizumab and in 13 of 15 patients treated with antihistamines. Our examination by immunostaining also revealed basophil infiltration of the CSU lesions, as in previous reports, but since most of our patients were already taking oral steroids, it was not considered appropriate to examine the relationship between basophil numbers in tissue and peripheral blood. Then, we used mouse model of contact hypersensitivity with a single application of oxazolone, which is known to stimulate basophil infiltration, and investigated basophil counts in the skin, peripheral blood, and bone marrow. In this model, a decrease in peripheral blood basophil numbers was observed one day after challenge, but not after 2 days, reflecting supplementation from the bone marrow. Indeed, when cultured basophils expressing GFP were transplanted into the peripheral blood, GFP-positive basophil numbers in the peripheral blood remained low even after 2 days of challenge. Despite differences among species and models, these results suggest that one reason for the decrease of basophils in the peripheral blood in CSU may involve migration of circulating basophils into the skin.